Profile of severe acute malnutrition children admitted at nutritional rehabilitation centre at tertiary care treatment centre of Gujarat - Prajapati, Nisha; Shah, Seema (International Journal of Contemporary Pediatrics, 2020)
Background: Severe acute malnutrition (SAM) may be major obstacle for India to achieve targeted Infant Mortality Rate and under five mortality rate. Malnutrition and infection form vicious cycle and contributes towards mortality. So, malnutrition prevention is major objective of government. Study of malnourished children helps to know aetiology and their response to treatment. The objective of study is to understand clinic-demographic profile of SAM children. Methods: It is retrospective secondary data analysis study. For the purpose of this analysis, we retrieved the data of all children with SAM admitted from 1 January, 2018 to 31 December, 2018 to NRC. At the NRC, a physician conducted a clinical examination in children to detect the presence/absence of medical complications during their admission and these data were available in case sheet. Results: A total of 162 children, aged 6-59 months were referred to the NRC. Around fourty seven percentage of children were in age group 6–12 months Majority of children were in age group of 7 months to one year of age. Majority of children were admitted based on weight of height criteria (Z score < 3SD). Mean admission weight is lower in female compare to male children. Conclusions: Faulty weaning practises and delay in weaning in some cases predisposes later half of infancy period to undernutrition. So, proper health education and good IYCF practices prevent children from undernutrition.